Efektivitas Penggunaan Media Kartu Warna Terhadap Keterampilan Menulis Pantun Siswa Sekolah Dasar - Hendra; Bahrun; Munir (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
This study aims to find out how the effectiveness of Wana Card media on students' rhyme writing skills in Indonesian language learning class V of SD Negeri Tille. This type of research is a quantitative experiment (pre-experimental). This design uses an experimental class given a learning model. After being given the treatment, a final test was given. The normality testing criteria is sig value > 0.05, the data is normally distributed, if sig < 0.05, the data is not normally distributed. From the test results, the Pretest value is 0.007 > 0.05 and the Post-test value is 0.07 > 0.05. From these tests, it can be concluded that the Pretest value is greater than 0.05 and the Post-test value is greater than 0.05. The homogeneity test results obtained Sig value α = 0.198, this means that the Sig value is greater than α (0.198 > 0.05) so that it can be concluded that the two groups are homogeneous. the hypothesis results obtained Sig (2.Tailed) = 0.000 meaning that H0 is rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.198 > 0.05). In the T test analysis, Sig < table or (0.198 < 1.267).